Smart Actions in Animation Based on Artificial Intelligence (AI)/ Tindakan Cerdas dalam Animasi Berbasis Artificial intelligence (AI) - DR. RR. Ella Evrita H, S.E, M.M, DR. RR. Ella Evrita H, S.E, M.M (Akademi Komunikasi SAE Indonesia, 2023)
Artificial intelligence (AI) has changed the face of the animation industry, giving animated characters the ability to act smarter and react to their environment. In this article, we explore how AI can be used in animation to create more realistic, adaptable, and intelligent characters. First, we'll discuss how animated characters use artificial intelligence to understand their surroundings, including object recognition, spatial understanding, and detecting environmental changes. It also describes how animated characters respond to their environment through emotional reactions and adaptive behaviors. Next, we'll examine how to use artificial intelligence features to create animated characters in various situations. This includes developing unique characters, modeling emotional responses, and predicting character movements. We also highlighted the importance of prioritizing environmental sustainability when applying AI technology to animation. Lastly, we highlight the importance of further development of AI technology and interdisciplinary collaboration in animation. It also highlighted the need for education and training in this area and explored the potential of AI in other industries. The research methods used are exploratory and descriptive methods also focusing on the development and exploration of AI concepts and applications in animation.